Embracing foreign nurses into Malaysia's health care system - Norsalawati, Ismail * (CodeBlue, 2023)
A former matron praises MOH’s decision to allow foreign nurses to work in Malaysian private hospitals amid nursing shortages. In 2021, Malaysia had 113,787 registered nurses, or 1:454 nurse-to-population ratio, far less than 1:300 ratio recommended by WHO.